Kandungan Mikrobiologi Air Baku di Wilayah Desa Perian Untuk Kebutuhan Air Minum Muara Muntai Kutai Kartanegara - Adawiyah, Rabiatul; Kurniawan, Deny (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
Clean water is an important role in life as a natural resource that has essential functions, one of which is for drinking water, if the microbiological bacteria content exceeds the standard, it will cause diarrhea. Data from the Kutai Kartanegara Regency Health Office in 2020 including the Muara Muntai District Health Center recorded 490 cases of diarrhea and 268 cases of diarrhea in toddlers. The purpose of the study was to conduct microbiological tests on clean water which is the raw source of drinking water in Perian Village, Kutai Kartanegara Regency. The method used is Descriptive method with laboratory examination, namely conducting two tests of E. Coli and Total Coliform in drinking water sources using the Colilert method of MPN/100mL units. The results of the E. Coli examination in spring water amounted to 161 MPN/100mL, borehole water 1 and 2 were not detected (0 MPN/100mL). Total Coliform content showed that spring water contained 2420 MPN/100mL, borehole 1 contained 299 MPN/100mL, borehole 2 contained 114 MPN/100mL. The conclusion from the research at three sample points of E. Coli parameters of borehole wells 1 and 2, still meet the standard, while for spring water test samples do not meet the standard. The Total Coliform parameter of spring water, borehole 1, and 2 did not meet the standard. Suggestions for the need for water treatment, and environmental management of water quality to comply with quality standards.